2020
DOI: 10.1002/aenm.202001035
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of High‐Nickel‐Layered Oxide Cathodes from Surface to Bulk: A Comprehensive Structural, Chemical, and Electrical Analysis

Abstract: Multiple applications of lithium‐ion batteries in energy storage systems and electric vehicles require highly stable electrode materials for long‐term battery operation. Among the various cathode materials, high‐Ni cathode materials enable a high energy density. However, cathode degradation accompanied by complex chemical and structural changes results in capacity and voltage fading in batteries. Cathode degradation remains poorly understood; the majority of studies have only explored the oxidation states of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(43 citation statements)
references
References 54 publications
1
41
1
Order By: Relevance
“…6a , two strain-relaxed regions can be observed, with one on the surface (marked by dashed square f) and the other one in the interior of the particle (marked by dashed square b). The results are contradictory to the prevailing surface-to-bulk phase transformation mode for layered cathodes, which believed that the degradation was initiated from the surface 61 , 62 . Although our investigated system is based on a highly strained material, which is different from most of the previously investigated materials, the synthesis of layered oxide cathodes generally involves the sophisticated process, which can actually induce many different kinds of native structural defects, especially during the large-scale manufacturing process that could easily suffer from temperature heterogeneity.…”
Section: Resultscontrasting
confidence: 72%
“…6a , two strain-relaxed regions can be observed, with one on the surface (marked by dashed square f) and the other one in the interior of the particle (marked by dashed square b). The results are contradictory to the prevailing surface-to-bulk phase transformation mode for layered cathodes, which believed that the degradation was initiated from the surface 61 , 62 . Although our investigated system is based on a highly strained material, which is different from most of the previously investigated materials, the synthesis of layered oxide cathodes generally involves the sophisticated process, which can actually induce many different kinds of native structural defects, especially during the large-scale manufacturing process that could easily suffer from temperature heterogeneity.…”
Section: Resultscontrasting
confidence: 72%
“…8a, b , the atomic percentage of Al 3+ decreased gradually from ~7 to 2% with an increase in etching depth up to 120 nm, which proves the gradient doping of Al 3+ . According to previous work 17 , 18 , Ni 2+ cation mixing and structure disintegration firstly start from the outer surface. For the interior of particles which are more stable than the surface, a small amount of Al 3+ is capable for alleviating Ni 2+ cation mixing.…”
Section: Resultsmentioning
confidence: 99%
“…Heteroatom doping was applied to stabilise the crystal structure of primary particles with an enhanced Li + diffusivity 15 , 16 . Because structure disintegration usually commences around the crystal surface 17 , 18 , and considering the specific capacity, an effective surface-enrichment gradient doping is required for this cathode. Theoretical calculations revealed that the doping efficiency is generally low because of easily formed dopant-containing electrochemical inert compounds on the particle surface 19 , 20 .…”
Section: Introductionmentioning
confidence: 99%
“…The pursuit of high energy density has driven the widespread application of layered lithium nickel manganese cobalt (NMC) oxides as positive electrode (PE) materials [1,2] of lithium ion batteries, especially those with high nickel ratio like NMC811. However, nickel-rich PEs su er from fast capacity decay and low cycling stability due to a multitude of degradation phenomena, among which a major one is the phase transition from the layered structures to disordered spinel and nally to rock-salt structures at low degrees of lithiation.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang [10] attributed almost all known problems of NCM811 to the release of lattice oxygen occurring in the irreversible phase transition of layered → spinel → rocksalt and suggested to focus on suppression of oxygen evolution for degradation mitigation. Ko et al [1] believed that the degradation stems from closely related chemical and structural changes, which cannot be interpreted independently. Apparently, a more clear picture of the degradation mechanisms is urgently needed, and further elucidation are expected from continuing experimental studies.…”
Section: Introductionmentioning
confidence: 99%